Generating semantically similar permutations of questions by clustering - Famili, Kurniawan Aryanto (2018)
With sophisticated machine learning techniques available to the public, many industry has used their own data to solve their own problems, including training chat bots. However, a lack of data is major concern when trying to train a bot for specific use-cases, such as a university FAQ-answering bot.